Autonomous motivation and action planning are longitudinally associated with physical activity during adolescence and early adulthood. (September 2021) - Courtney, Jimikaye B.; Li, Kaigang; Nelson, Tracy L.; Nuss, Kayla J.; Haynie, Denise L.; Iannotti, Ronald J.; Simons-Morton, Bruce G.
Abstract: We examined the associations of autonomous motivation, controlled motivation, and physical activity (PA) planning with PA participation over six years across the adolescent-to-adult transition. Participants from the NEXT Generation Health Study, a nationally representative cohort study of U.S. 10th graders (N = 2785), completed surveys yearly from 2010 to 2016 (four years post-high school). This study used data from Waves 2 (W2) through 7 (W7). Data were analyzed using growth models accounting for the complex survey design and controlling for sex, race/ethnicity, and body mass index. A piecewise growth model with two pieces (Piece 1: W2–W4; Piece 2: W4–W7) indicated that PA declined during late adolescence (W2–W4) ( b  = −0.31, β  = −0.22, p  < .001), but did not decline after the transition into early adulthood (W4–W7) ( b  = −0.08, β  = −0.04, p  = .052). Autonomous motivation was positively associated with PA at all waves ( b  = 0.23–0.33, β  = 1.90–4.37, p  < .001). Controlled motivation was only positively associated with PA at W3 (12th grade) ( b  = 0.13, β  = 1.54, p  = .011). PA planning varied significantly between individuals and significantly predicted PA ( b  = 0.44, β  = 0.21, p  < .001). Although PA decreased significantly during late adolescence, PA did not decrease significantly after transitioning into early adulthood (one to four years post-high school). Elevated autonomous motivation and PA planning were consistently and significantly associated with higher PA, suggesting that these may be useful intervention targets during this adolescent-to-adult transition. Highlights: Physical activity decreased from 11th grade to one-year post-high school. Physical activity did not change from one to four years post-high school. Autonomous motivation and activity planning were positively associated with physical activity. Controlled motivation was only positively associated with physical activity in 12th grade. Autonomous motivation and activity planning may be useful intervention targets.